Comparison of the Effects of Supine and Prone Positions on Oxygen Saturation and Vital Signs in Premature Infants: A Crossover Clinical Trial - Hamid Torabian; Saeed Alinejad; Akram Bayati; Fatemeh Rafiei; Sharareh Khosravi (Mashhad University of Medical Sciences, 2019)
Background: Positioning of premature newborns significantly affects their health status. However, the most suitable position remains controversial. The current study aimed to compare the effect of supine and prone positions on oxygen saturation and vital signs in premature newborns. Methods: In this crossover clinical trial, a total of 22 newborns admitted to the Neonatal Intensive Care Unit (NICU) of Amir Kabir Hospital in Arak, Iran, were selected through purposive sampling technique, and then randomly assigned into groups 1 and 2. Newborns in group 1 were first placed in a prone position (i.e., the first period for 3 h), and then in a supine position (i.e., the second period for an additional 3 h). The reverse procedure was applied to the intervention group 2. Heart rate, respiratory rate, and oxygen saturation were measured and recorded every 15 min. Results: The mean oxygen saturation in the prone position (96.164±0.148) was higher than in the supine position (90.479±0.513; P=0.0001). The mean heart rate in the prone position (138.24±1.87 beats/min) was lower than that in the supine position (147.48±1.597 beats/min; P=0.0001). The mean respiratory rate in the prone position (40.430±0.504 breaths/min) was lower than that in the supine position (46.773±0.685 breaths/min; P=0.0001). Conclusion: The current study demonstrated that the prone position put the newborn admitted to NICU in a more stable condition. However, the selection of the best position must be made based on the newborn's health status and situation.